Investigation of Load Frequency Control with Optics Inspired Optimization Algorithm in a Four Area Power System with HVDC Connection Line - Yildiz, Suleyman; Yildirim, Burak; Ozdemir, Mahmut Temel (Ieee, 2019)
It is considerably important that the energy is presented to consumer as quality and confidential in the production of electrical energy. It is expected to continuously track and control the supply and demand relationship between producers and consumers by reliable power system. In this sense, the most significant parameter to be controlled in interconnected systems is the system frequency. The frequency deviation must be kept within certain limits in the power system; this is realized by maintaining the balance of power generation and power consumption. In this study, the effect of High Voltage Direct Current (HVDC) transmission lines parallel to Alternative Current (AC) transmission line is investigated on power system frequency control in the High Voltage Alternating Current (HVAC) transmission line and connected to each other in a power system formed by sub-areas. For that purpose, respectively a multi area power system in accordance with Turkey's facts were modeled in MATLAB in this study. The effects of adding one and more HVDC transmission lines to this power system on load frequency control were investigated. The examination was fulfilled for three cases. These are the conditions where there is no DC connection, the ideal DC connection and the DC connection with PLL. In this study, the gain of controllers were determined by Optics Inspired Optimization (OIO) method. The determined controller gains were used for the time domain responses in the generated model and also results were analyzed.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: HVDC; HVAC; Optics Inspired Optimization; Automatic Generation Control; Load-Frequency Control